Regional income redistribution and risk-sharing: lessons from Argentina - Cont, Walter (2017)
This paper estimates redistribution and risk-sharing across provinces in Argentina during the 1995–2010 period as a result of the national budget. We find that the aggregate national budget (expenditure, transfers and their corresponding revenues) reduces differences in the per capita provincial Gross Geographic Product by 5% in the long term, and stabilizes such differences by 10%. The redistributive tool is national expenditure, while automatic intergovernmental transfers are almost neutral and tax revenues amplify regional disparities. The quantitative effects are somewhat modest in comparison with those achieved in developed countries. Regressive taxation is the key difference with developed countries.